An Essay on Consent(less) Police Searches - Daniel L. Rotenberg (Washington University Law Quarterly, 1991)
Police searches that are publicly authorized must meet the minimum requirements of the United States Constitution. The fourth amendment requires that searches be reasonable, but often they must also be based on probable cause, conducted pursuant to a search warrant, and confined by particularity of both place to be searched and item to be seized. The one irreducible factor, however, is reasonableness. So much for the obvious. Consent searches present a different story; they are privately authorized. For this reason, one could argue, no constitutional limitation-neither the fourth amendment nor the two due process amendments-is implicated. Of course, this is not the law; the Supreme Court has held that consent searches must satisfy the reasonableness standard of the fourth amendment. The Court, however, has not imposed a probable cause prerequisite on consent searches; it has neither required a showing of exigency, nor has it insisted that an administrative search warrant be obtained, an area search authorization be established, or that reasonable suspicion be shown. Neither public authorization nor prior suspicion of the slightest degree by the police department, or even the policeman himself, is a condition to a police officer's approaching a citizen-even at the entrance to his home-and requesting consent to search. Given consent, the search power is awesome. A defender of the faith might respond, "So what? If a person consents to have his fourth amendment interests searched by police, then obviously the search is reasonable." Perhaps. What if, however, consent searches typically are not based on actual consent? A case can be made that the current consent search is not only mislabeled, but is constitutionally unreasonable. This Article tries to make that case and to suggest some changes.
Keywords: Searches & seizures (Law)